PROFIL LANJUT USIA (Studi Tentang Proses Adaptasi Lanjut Usia di Panti Sosial Tresna Werdha Husnul Kotimah Pekanbaru) - M. Arif Agung Putra; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The research was conducted at The Werdha Husnul Khotimah Orphanage of Pekanbaru City of Riau Province. The purpose of this study is to find out the factors behind the elderly living in tresna werdha Husnul khotimah social housing and to find out the process of adaptation of the elderly in tresna werdha Husnul khotimah social housing. Researchers used descriptive qualitative analysis by assigning 6 study subjects who were taken intentionally with the criteria set by the researchers. Purposive sampling of subjects with data collection techniques such as observation, interview and documentation. The result of this study is that there are several backgrounds of elderly People Living in Werdha Husnul Khotimah Orphanage, starting from an economic background to be one of the causes of the many elderly who moved to Werdha Orphanage, then from a social background is also one of the strong causes of the elderly can move to Werdha Orphanage because of the social circumstances they do not support to stay in their previous neighborhood and have to move to Werdha Orphanage. In addition, there are several elderly adaptation processes in Panti Werdha Husnul Khotimah namely adaptations within the group such as interactions between individuals and groups or between individuals who create each other, adaptation of values and norms within the group. And also in the elderly who live in a Werdha orphanage based on their own desires and without any coercion, it will consider the Werdha orphanage as a place like a house that can give a sense of comfort. Keywords: Elderly, Factors Behind The Stay and Adaptation Process.